Investigation on the genus Squalus in the Sardinian waters (Central-Western Mediterranean) with implications on its management - BELLODI, ANDREA; PORCU, CRISTINA; CAU, ALESSANDRO; MARONGIU, MARTINA FRANCESCA; MELIS, RICCARDO; MULAS, ANTONELLO; PESCI, PAOLA; FOLLESA, MARIA CRISTINA; CANNAS, RITA (Mediterranean Marine Science, 2018)
In the Mediterranean Sea, in addition to the two historically known species belonging to the Squalus genus, a third species, Squalus megalops, has been reported. Considering the high level of morphologic similarity of this species with the native species S. blainville, this study aims to evaluate the Central-Western Mediterranean spurdog population in order to test the hypothesis of the presence of two distinct species S. blainville and S. megalops. A total of 137 spurdogs, caught in the Sardinian waters, were analyzed morphologically and genetically after their subdivision into two groups depending on the number of the lateral processes in the chondrocranium basal plate. The CAP analysis, employing all body and chondrocranial measurements, revealed no clear segregation among the a priori assigned groups with a high misclassification percentage. Besides, no evident dissimilarities in teeth and dermal denticle morphology between the two groups were observed. All the 18 specimens which were genetically analyzed, by sequencing of the mtDNA marker COI, clustered together resulting to be S. blainville. All the obtained results indicated the presence, in the study area, of only one species, ascribable to S. blainville.